Argumentasi Ibnu Rusyd tentang Eskatologi - Pridandi, Pirhad (Jurnal Riset Agama, 2023)
This study aims to analyze the views of Ibn Rushd about the afterlife which in terms is called eschatology. This research uses a library research method with two sources, namely primary sources and secondary sources. The primary source in question is data from a book by Ibn Rushd entitled Tahafut At-Tahafut, while secondary sources are data taken from books, previous research articles, and things related to the object of discussion. The results of the study Ibn Rushd is one of the philosophers and thinkers from Andalusia who argues that the spiritual will get a reward in the form of pleasure as a form of reward or vice versa, getting torture in the afterlife. Ibn Rushd also has the view that death is a state of separation of spirit and body. Because the body is actually made of soil, it will return to the ground, while the human spirit will go to the afterlife.